Development of a diarrhea management model based on health belief model and symptom management theory to improve mothers’ ability in home-based care of under-five children - Mariyam Mariyam; Yuni Sufyanti Arief; Makhfudli Makhfudli; Nuzul Qur'aniati; Ilya Krisnana (Universitas Airlangga, 2026)
Introduction: Diarrhea remains a leading cause of mortality in children under five, often exacerbated by suboptimal home-based management and inaccurate maternal symptom evaluation. Objective: This study aims to develop and analyze a diarrhea management model based on the Health Belief Model (HBM) and Symptom Management Theory (SMT) to improve mothers' ability to care for under-five children at home. Methods: A quantitative study using a structural equation modeling (SEM) approach was conducted. Data were collected from 130 mothers of under-five children using structured questionnaires. Inclusion criteria were mothers of under-five children with acute diarrhea without dehydration or with mild to moderate dehydration; primary caregivers; and able to read and write. Exclusion criteria included mothers with hearing or visual impairments and mothers of children with comorbid conditions. The sampling was conducted using a non-probability sampling technique, specifically purposive sampling. The exogenous variables included maternal, child, environmental, and healthcare provider factors, while symptom experience and belief-based management served as mediating variables. Results: Symptom experience was directly influenced by maternal factor (t=5.254, P-value<.001), child factor (t=1.989, P-value<.001), environmental factor (t=5.185, P-value<.001), and healthcare provider factor (t=2.605, P-value=.046). Symptom experience significantly triggered belief-based management (t=10.530, P-value<.001), with symptom evaluation being the strongest indicator (t=34.116). Ultimately, belief-based diarrhea management showed a strong positive influence on mothers' ability to care for under-five children at home (t=18.027, P-value<.001). Conclusion: Maternal caregiving competence is significantly improved when diarrhea management protocols are integrated with health belief constructs. Interventions should prioritize enhancing mothers' internal health beliefs and clinical symptom evaluation skills rather than focusing solely on knowledge transfer. Keywords: diarrhea; health belief model; mothers; pediatric nursing; symptom assessment